2011
DOI: 10.1002/fut.20469
|View full text |Cite
|
Sign up to set email alerts
|

Price discovery and investor structure in stock index futures

Abstract: Previous literature on price discovery in stock index futures and spot markets neglects the role of different investor groups. This study relates time-varying spotfutures linkages studied within a VECM-DCC-GARCH framework to changes in the investor structure of the futures market over time. Empirical results suggest that during the dominance of presumably uninformed private investors, the futures market does not contribute to price discovery. By contrast, there is evidence of information flows from futures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 66 publications
5
58
1
Order By: Relevance
“…Although gold futures account for a smaller proportion of total turnover, several studies of other markets show that futures play an important role in price discovery (Bohl et al, 2011;Boyd & Locke, 2014;Dolatabadi et al, 2015;Rosenberg & Traub, 2009), although not in all settings (e.g., Cabrera et al, 2009). Despite the enormous size of the international gold market, somewhat surprisingly, relatively little is known about how information is incorporated into gold prices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gold futures account for a smaller proportion of total turnover, several studies of other markets show that futures play an important role in price discovery (Bohl et al, 2011;Boyd & Locke, 2014;Dolatabadi et al, 2015;Rosenberg & Traub, 2009), although not in all settings (e.g., Cabrera et al, 2009). Despite the enormous size of the international gold market, somewhat surprisingly, relatively little is known about how information is incorporated into gold prices.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that futures contracts lead their respective underlying assets in price discovery (Bohl et al, 2011;Rosenberg & Traub, 2009), yet this relationship has not been confirmed in the gold market despite its immense size and economic impact. Cabrera et al (2009) find that foreign exchange spot quotes consistently lead foreign exchange futures prices.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Nonetheless, while smaller, it is reasonable to wonder if given the more transparent nature of futures and options markets whether these might not in fact be a more efficient and informative market in terms of price setting. The consensus in literature for stock and currency futures and options is that futures markets lead spot markets in terms of information and price discovery (see Bohl, Salm, and Schuppli (2011), Rosenberg and Traub (2009)). Despite its importance, with the gold market representing approximately the same gross size as the US--Australian and US -Canadian dollar foreign exchange markets (based on 2010 data in Bank for International Settlements (2011)) we find surprisingly little research has been undertaken on this area in the gold market.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Nonetheless, while smaller, it is reasonable to wonder if given the more transparent nature of futures and options markets whether these might not in fact be a more efficient and informative market in terms of price setting. The consensus in literature for stock and currency futures and options is that futures markets lead spot markets in terms of information and price discovery (see Bohl, Salm, and Schuppli (2011), Rosenberg and Traub (2009)). Despite its importance, with the gold market representing approximately the same gross size as the US--Australian and US -Canadian dollar foreign exchange markets (based on 2010 data in Bank for International Settlements (2011)) we find surprisingly little research has been undertaken on this area in the gold market.…”
Section: Introductionmentioning
confidence: 99%